Superiority of measuring apolipoprotein B to conventional lipid profile predicting risk of acute coronary syndrome in young people. - Aditya, GP; Bari, MA; Bari, MS (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2011 Oct;20(4):578-85 The abstract of this article is available on the PubMed website